2020
DOI: 10.1007/s11325-020-02160-8
|View full text |Cite
|
Sign up to set email alerts
|

Cluster analysis identifies a pathophysiologically distinct subpopulation with increased serum leptin levels and severe obstructive sleep apnea

Abstract: Purpose To investigate the different pathophysiologies of obstructive sleep apnea (OSA) phenotypes using cluster analysis. Differences between leptin/adiponectin levels in the resulting OSA phenotypes were also examined. Methods In total, 1057 OSA patients were selected, and a retrospective survey of clinical records, polysomnography results, and blood gas data was conducted. Patients were grouped into four clusters by their OSA severity, PaCO2, body mass index (BMI), and sleepiness. A k-means cluster analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…e teacher communicated with the students to learn more about the completion of the students' music works, to answer the questions one by one, and solve the problem of less interaction between teachers and students before [18]. e fourth week class form was Superstar Learning and Dingding live teaching.…”
Section: After-school Homeworkmentioning
confidence: 99%
“…e teacher communicated with the students to learn more about the completion of the students' music works, to answer the questions one by one, and solve the problem of less interaction between teachers and students before [18]. e fourth week class form was Superstar Learning and Dingding live teaching.…”
Section: After-school Homeworkmentioning
confidence: 99%
“…They found that the probabilities of having hypertension, diabetes, and cardiovascular disease were the highest in the minimally symptomatic group [ 4 ]. Kozu et al divided patients with OSA into four clusters according to OSA severity, PaCO 2 , body mass index, and sleepiness, and found different serum C-reactive protein and leptin levels among clusters, which revealed different pathophysiological backgrounds of OSA [ 5 ]. A recent study identified nine clusters according to 10 clinically relevant and objectively identified comorbidities in patients with moderate-to-severe OSA, which found different cardiovascular risk, adherence to positive airway pressure, and long-term survival among clusters [ 6 ].…”
Section: Introductionmentioning
confidence: 99%